Sosialisasi Dampak Limbah Tailing dan Pelatihan Pembuatan Kolam Pengendapan Tailing di Tambang Emas Rakyat Juriya - Ninasafitri Ninasafitri; Fitryane Lihawa; Vivi Dia Afrianti Sangkota; Dicky Rahmansyah; Airin B Nteseo; Hesti Uno; Jemi Rikarno (Universitas Negeri Gorontalo, 2026)
Small-scale mining in Juriya Village has long been the main source of income for the community. However, the traditional mining methods used still disregard the principles of good environmental management, resulting in environmental pollution, particularly tailings waste that has contaminated nearby rivers. Survey results at the mining site show that several mining drums are not equipped with tailings settling ponds that meet standards, resulting in tailings waste seeping into river flows. To address this issue, community service activities were carried out with the aim of increasing the understanding and awareness of the community and miners regarding the impact of tailings pollution and the importance of responsible waste management. These activities included socialization, education, and training on the construction of tailings settling ponds. The results of these activities showed an 88% increase in community understanding of the environmental hazards of tailings, as well as increased community knowledge about the process of constructing compartmentalized tailings settling ponds. This demonstrates the important role of socialization, education, and training in effective tailings waste management efforts.